A Comparative Study of Chitosan and Glucosamine Isolated from Local Mushroom ‘Lenahathu’ (Schizophyllum Commune) and Oyster Mushroom (Pleurotus Ostreatus) - Kalutharage, N. K.; Rathnasinghe, D. L. (University of Jaffna, 2019)
The use of mushroom as a raw material to obtain chitosan and glucosamine was investigated at laboratory level. Properties of chitosan extracted from local mushroom “lenahathu” (Schizophyllum commune) and common oyster mushroom (Pleurotus ostreatus) were compared. Isolation process of chitosan involved de-mineralization, de-proteinization, de-acetylation and de-coloration steps. The physico-chemical properties of chitosan such as solubility, moisture content, ash content, N content, fat binding capacity (FBC), water binding capacity (WBC) and degree of de-acetylation (DD) of chitosan samples extracted from Schizophyllum commune and Pleurotus ostreatus were analysed. The purity of two glucosamine samples were analysed by spectrophotometrically and scan electron microscope (SEM). The values for percentage yield, solubility, moisture content, ash content, N content, WBC were 1.73 ± 0.05% and 1.22 ± 0.01%, 7.38 ± 0.10% and 3.41 ± 0.14%, 6.39 ± 0.20% and 8.16 ± 0.42%, 8.19 ± 0.04% and 1.63 ± 0.05%, 11.31% and 3.02%, 387.13 ± 15.57% and 402.57 ± 12.78% respectively for chitosan samples from Schizophyllum commune and Pleurotus ostreatus. FBC were varied approximately 250% - 350% in coconut oil, soy bean oil and sunflower oil. Chitosan and glucosamine were characterized using Fourier Transformed Infra-Red (FT-IR) spectroscopy. DD% of chitosan using FT-IR and conductometric titration were 53.10% and 60.68% respectively for two species. The yield and purity of glucosamine sample of Schizophyllum commune were 95.70% and 0.97 ± 0.08%. However the yield and purity of glucosamine sample of Pleurotus ostreatus were 58.14% and 0.52 ± 0.04% respectively. According to results Schizophyllum commune could be a good alternative to extract chitosan and an important drug glucosamine.
Keywords: Chitosan; glucosamine; mushroom; Schizophyllum commune; Pleurotus ostreatus